AN IMPROVED METHODOLOGICAL MODEL FOR TEACHING THE COURSE “MODERN HISTORY OF UZBEKISTAN” ON THE BASIS OF IT (Web of Teachers: Inderscience Research, 2026)
This article analyzes the theoretical and methodological foundations and practical mechanisms of teaching the course Modern History of Uzbekistan on the basis of information technologies. An improved methodological model, developed on the basis of modern digital tools, interactive methods, and a competency-based approach in teaching the history of the independence period, is recommended. The research results show that lessons organized on the basis of IT increase educational effectiveness.